PROGRAMMED LEARNING AS SOLUTION FOR SCHOOLS WITH COMBINED CURRICULUM TO WIN ENGLISH ONLINE NATIONAL EXAMINATION - Ludwina Lucky Wibakti (IJIET (International Journal of Indonesian Education and Teaching), 2018)
Programmed learning which consists of specially designed syllabus and CALL (Computer-Assisted Language Learning) was designed to win English Online National Examination at John Pauls School. It emerged as an answer to the employment of combined curriculum at Satuan Pendidikan Kerjasama School like John Pauls School where Cambridge curriculum is applied to prepare the students to take Cambridge International Examination as added value of the school and national curriculum which is provided at the final grade of each level, grade 9 and grade 12. The application of Online National Examination triggers the empowerment of information technology in formulating, designing, applying, evaluating and improving the Programmed Learning to its effectivity and efficiency. The success of the Programmed Learning application at John Pauls School may inspire other schools with combined curriculum to do similar things.DOI:https://doi.org/10.24071/ijiet.2018.020109